Novel mutations in PLCZ1 cause male infertility due to fertilization failure or poor fertilization. Issue 2 (12th February 2020) - Yan, Zheng; Fan, Yong; Wang, Fei; Yan, Zhiguang; Li, Menghui; Ouyang, Jie; Wu, Ling; Yin, Mingru; Zhao, Jilang; Kuang, Yanping; Li, Bin; Lyu, Qifeng
Abstract: STUDY QUESTION: Do sperm-specific phospholipase C zeta ( PLCZ1 ) mutations account for male infertility due to fertilization failure? SUMMARY ANSWER: Six novel mutations and one reported mutation in PLCZ1 were identified in five of 14 independent families characterized by fertilization failure or poor fertilization, suggesting that these mutations may be responsible for fertilization failure in men exhibiting primary infertility. WHAT IS KNOWN ALREADY: PLCZ1 is essential for the induction of intracellular calcium (Ca 2+ ) oscillations and the initiation of oocyte activation during mammalian fertilization. However, genetic evidence linking PLCZ1 mutations with male infertility remains limited. STUDY DESIGN, SIZE, DURATION: Fourteen unrelated primary infertility patients were recruited into this study from January 2016 to December 2018; the patients exhibited total fertilization failure or poor fertilization, as evidenced by ICSI and sperm-related oocyte activation deficiencies identified in mouse oocyte activation assays. PARTICIPANTS/MATERIALS, SETTING, METHODS: Genomic DNA samples were extracted from the peripheral blood of patients. The whole exons of PLCZ1 were sequenced by Sanger sequencing. The PLCZ1 sequences were aligned by CodonCode software to identify rare variants. The ExAC database was used to search for the frequency of corresponding mutations. The pathogenicity of identified variants and their possible effects on the protein were assessed in silico. PLCZ1 protein levels in semen samples were evaluated by western blotting. Oocyte activation ability was assessed by the injection of wild-type and mutant PLCZ1 cRNAs into human mature metaphase II (MII) oocytes in vitro . MAIN RESULTS AND THE ROLE OF CHANCE: We identified six novel mutations and one reported mutation in PLCZ1 among five affected individuals. In addition to four novel missense mutations, two new types of genetic variants were identified, including one in-frame deletion and one splicing mutation. Western blot analysis revealed that PLCZ1 protein expression was not observed in the semen samples from the five affected patients. Microinjection with the PLCZ1 cRNA variants was performed, and a significant decrease in the percentage of pronuclei was observed for four novel missense mutations and one novel in-frame deletion mutation, suggesting that these mutations have a deleterious influence on protein function. By artificial oocyte activation treatment, the fertilization failure phenotypes of four affected patients were successfully rescued and three healthy babies were delivered. LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: We screened only the whole exons of PLCZ1 . Additional possible mutations in the non-coding region of PLCZ1 should be further studied. WIDER IMPLICATIONS OF THE FINDINGS: Our study not only further confirms the important role of PLCZ1 in human fertilization but also expands the mutational spectrum of PLCZ1 associated with male infertility, which provides a basis for assessing genetic variation in PLCZ1 as a potential diagnostic marker for infertile men suffering from fertilization failure. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by the National Natural Foundation of China (81 571 486 and 81 771 649). All authors have no conflicts of interest to declare.